Insider threats - Arduin, Pierre-Emmanuel (Advances in information systems set, 2018)
An information system may be regarded as an organized set of resources, both technological and human. Security should take this specificity into consideration in order to ensure an overall security of information systems. The security of information systems is usually tackled in a technological perspective. This book proposes to focus not only on information systems' security in a technological perspective, but also in a human, managerial and organizational perspective